2014
DOI: 10.3168/jds.2014-7954
|View full text |Cite
|
Sign up to set email alerts
|

Antialcoholic liver activity of whey fermented by Lactobacillus casei isolated from koumiss

Abstract: Whey fermented liquid (WFL) was studied for its hepatoprotective effects by using chronic alcohol-induced mice. Whey fermented liquid, prepared by inoculating whey with 4% (vol/vol) Lactobacillus casei and then incubating at 41°C for 8h, was used to orally treat alcohol-induced mice at 3 dosages for 5 wk. Ethanol consumption significantly reduced the activity of superoxide dismutase and glutathione peroxidase, while lowering glutathione content and increasing levels of aspartate aminotransferase, alanine amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
10
0
2
Order By: Relevance
“…On the other hand, Zhao et al (2014) studied the effect of fermented whey by a L. casei strain on the anti-alcoholic liver activity of chronic alcohol-induced mice and observed that the pathological characteristics of livers of alcohol-receiving mice were improved by the administration of fermented whey. Kume et al (2012) studied the effect of an enteral formula containing whey peptides and fermented milk on inflammation produced by concanavalin A-induced hepatitis.…”
Section: Health-promoting Effects Of Fermented Whey Productsmentioning
confidence: 98%
“…On the other hand, Zhao et al (2014) studied the effect of fermented whey by a L. casei strain on the anti-alcoholic liver activity of chronic alcohol-induced mice and observed that the pathological characteristics of livers of alcohol-receiving mice were improved by the administration of fermented whey. Kume et al (2012) studied the effect of an enteral formula containing whey peptides and fermented milk on inflammation produced by concanavalin A-induced hepatitis.…”
Section: Health-promoting Effects Of Fermented Whey Productsmentioning
confidence: 98%
“…A fermented whey produced by its inoculation with traditional homemade Kazak yoghurt showed an anti-atherosclerotic effect in rabbits [35]. Fermented whey produced by the inoculation of whey with Lactobacillus plantarum DK211 (isolated from kimchi) showed an anti-obesity effect in rats [36], and when L. casei was used, the fermented whey showed hepatoprotective effects in chronic alcohol-induced mice [37].…”
Section: Ace-inhibitory Activity In Fermented Wheymentioning
confidence: 99%
“…; Zhao et al . ). Further, some LAB strains with antimicrobial activity isolated from airag or koumiss have been reported (Batdorj et al .…”
Section: Introductionmentioning
confidence: 97%